Ge-rich SiGe thin film deposition by co-sputtering in in-situ and ex-situ solid phase crystallization for photovoltaic applications. (December 2016) - Shahahmadi, S.A.; Aizan Zulkefle, A.; Hasan, A.K.M.; Rana, S.M.; Bais, B.; Akhtaruzzaman, M.; Alamoud, A.R.M.; Amin, N.
Abstract: This study investigates the properties of high Ge content silicon-germanium thin films in the non-hydrogenated state (Ge-rich SiGe) deposited on glass by RF magnetron co-sputtering in both in-situ and ex-situ solid phase crystallization (SPC) at various temperatures, such as RT to 550 °C. The structural and optical characteristics of SiGe films have been explored systematically by optimizing growth temperature. Atomic composition of films was determined by EDX, which showed up to 77 at% of Ge. Structural properties were characterized by XRD, which revealed all samples to be in amorphous nature. The results from Raman and UV–VIS–IR transmittance measurements showed that the properties of amorphous Si0.23 Ge0.77 films improved at 450 °C in both in-situ and ex-situ SPC processes. In addition, EDX exposed an advantage of in-situ process over ex-situ due to the incorporation of oxygen during ex-situ thermal annealing. Possible deposition at low substrate temperature as found here suggests that these Si0.23 Ge0.77 films have a substantial potential to be used in thin film Si-based solar cells.